The Kurdish National Movement in Turkey : From Protest to Resistance. - Gunes, Cengiz (Taylor & Francis, 2011)
This book provides an interpretive and critical analysis of Kurdish identity, nationalism and national movement in Turkey since the 1960s. By raising issues and questions relating to Kurdish political identity and highlighting the ideological specificity, diversity and the transformation of Kurdish nationalism, it develops a new empirical dimension to the study of the Kurds in Turkey. Cengiz Gunes applies an innovative theoretical approach to the analysis of an impressively large volume of primary sources and data drawn from books and magazines published by Kurdish activists, political parties.